Nickel-vanadium impregnated to hydrotalcite for hydrocracking of waste cooking oil - Lenny Marlinda; Sugeng Priyanto; Peri Oktiarmi; Maja Pranata Marbun; Aisha Andini Indira Dewi; Sudibyo Sudibyo; Indri Yati; Abdul Aziz; Reva Edra Nugraha; Muhammad Al Muttaqii (Center of Biomass & Renewable Energy (CBIORE), 2026)
Hydrotalcite (HT) is a type of clay mineral belonging to the group of layered double hydroxides (LDHs) or anionic clays, which has a layered structure like brucite (Mg(OH)₂), but some of the divalent cations (such as Mg²⁺) are replaced by trivalent cations (such as Al³⁺). HT as a heterogeneous catalyst is particularly attractive because it is easy to separate and resistant to high temperatures. HT as a catalyst can be used in hydrocracking reaction to produce biofuel. Metal impregnation on HT is very promising to enhance catalytic activity especially with the bifunctional mechanism of catalyst. Ni-V metal impregnation has been successfully carried out on HTc using wet impregnation method which is indicated by the results of X-Ray Diffraction (XRD) which shows the emergence of typical peaks of both metals and HTc in 2θ = 35‒70⁰ for HTc, 2θ = 37.22⁰ (NiO) and 37.35⁰ (V2O5) regions, 2θ = 43.58⁰ for NiO, 2θ = 61.26⁰ (V) and 63.07⁰ (Ini). Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX) show a shape that is consistent with the characteristics of HT, namely the shape of the particles layered overlapping each other. In addition, the particle size of HTc is quite small with a scale of 1 μm indicating a particle size of hundreds of nanometers. EDX mapping shows that Ni and V have been dispersed evenly on the HTc surface. Based on the results of N2 adsorption-desorption isotherms, it shows that mesopores are formed which are characterized by hysteresis loops. Ni-V metal impregnation increases the surface area up to 19.915 m2/g and the pore diameter up to 37,642 nm. The results of the Waste Cooking Oil (WCO) hydrocraking reaction show that Ni-V metal impregnation can reduce the carboxylic acid composition up to 67.81% and increase hydrocarbons up to 15% at 10% Ni-V/HTc 1:2.